(untitled) (Eurasian Research Bulletin, 2022)
Nitrogen is a colorless, tasteless and odorless gas that plays an important role in human and living life. It is one of the most abundant elements and makes up 1.10-2.0% of the mass of the earth’s crust. The main part is in the atmosphere (75.6% by mass, 78.09% by volume) and is equal to 4×108 m3. Found in the air, in rivers, seas and oceans. In the Earth’s crust, it forms three basic units: free, minerals, and ions. It is recorded in the form of industrial sodium nitrate and potassium nitrate, in the gas clouds of comets, in the solar atmosphere. Nitrogen is present in all living things and contains up to 17% of the protein nitrogen, which is 3% of the total in the human body. Nitrogen is involved in the metabolism of nature, and its amount in the soil is formed due to the activity of nitrogen-fixing bacteria or microorganisms. Plants and microorganisms that absorb atmospheric nitrogen and convert it into nitrogen-fixing compounds together provide 200-500 kg of nitrogen per hectare per year